The Role of Overweight and Obesity on Bone Health in Korean Adolescents with a Focus on Lean and Fat Mass - Kim, Hwa Young; Jung, Hae Woon; Hong, Hyunsook; Kim, Jae Hyun; Shin, Choong Ho; Yang, Sei Won; Lee, Young Ah (Journal of Korean medical science, 2017)
As the associations between pediatric overweight/obesity and bone health remain controversial, we investigated the effects of overweight/obesity as well as lean mass (LM) and fat mass (FM) on bone parameters in adolescents. Bone parameters were evaluated using dual-energy X-ray absorptiometry (DXA) data of 982 adolescents (aged 12-19 years) from the Korea National Health and Nutrition Examination Survey (2009-2010). Z-scores for LM, FM, bone mass, bone mineral density (BMD), and bone mineral apparent density (BMAD) using Korean pediatric reference values were used for analysis. Adolescents with overweight/obesity had significantly higher bone mass and density of the total-body-less-head (TBLH), lumbar spine, and femur neck than underweight or normal-weight adolescents (P < 0.001) after adjusting for vitamin D deficiency, calcium intake, and insulin resistance in both sexes. LM was positively associated with bone parameters at all skeletal sites in both sexes (P < 0.001). FM was negatively related to TBLH BMD in boys (P = 0.018) but was positively associated to BMD and BMAD of the lumbar spine and femur neck in girls. In conclusion, overweight/obesity and LM play a positive role in bone health in adolescents. The effect of FM on bone parameters is sex- and site-specific.